Clinical factors associated with invasive pulmonary aspergillosis in patients with severe fever with thrombocytopenia syndrome: analysis of a 6-year clinical experience - Wang, Huan; Luo, Miao; Fisher, David; Pronyuk, Khrystyna; Musabaev, Erkin; Thu, Hien Nguyen Thi; Ye, Pian; Zhao, Lei (Frontiers in Microbiology, 2024)
Background: Invasive pulmonary aspergillosis (IPA) typically occurs in immunocompromised individuals. Severe fever with thrombocytopenia syndrome (SFTS) patients are typically characterized with fever, thrombocytopenia, and leukopenia. These patients typically present with dysregulation of cellular and humoral immunity, which may predispose them to IPA. Our study aimed to identify risk factors for SFTS-associated IPA and evaluate its associated prognostic impact. Methods: We conducted a cohort study between January 2017 and December 2022 in a tertiary hospital in Wuhan City, China. SFTS patients were divided into a SAPA group and a non-SAPA group according to whether they were coinfected with aspergillosis or not. The independent risk factors for SAPA group were determined by multivariate logistic regression. ROC analysis was used to assess the statistical value of parameters to predict SAPA patients. The survival analysis was carried out using the Kaplan-Meier (KM) method.Results: Of the 269 hospitalized SFTS patients enrolled in the study, 118 (43.87%) cases were diagnosed with SAPA with an average age of 65.71±9.7 years. Multivariate logistic regression analysis revealed that age, neurological complications, serum severe fever with thrombocytopenia syndrome virus (SFTSV) RNA loads, the white blood cell count (WBC), platelet count (PLT), albumin (ALB) and globulin (GLB) concentrations, cardiac Troponin I (c-TNI) as complementary risk factors for the development of IPA in SFTS patients. The risk score is calculated as 5 times Age, plus 6 times neurological complications, plus 10 times RNA (log), plus 5 times WBC, minus 5 times PLT, minus 5 times ALB, plus 5 times GLB, plus 6 times cTNI. ROC curve analysis showed that the area under the ROC curve (AUC) represented a risk score of 0.837 (95% CI: 0.789-0.885, p < 0.001) for predicting IPA in SFTS patients. The average length of hospitalization in the SAPA group was more prolonged than non-SAPA. The mortality rates of SAPA and non-SAPA groups are significantly different, 25.42% (SAPA) and 3.97% (non-SAPA), respectively (p < 0.05).SFTS patients with IPA have high morbidity and mortality. Early monitoring of neurological complications, SFTSV RNA loads, WBC, PLT, ALB, GLB, and c-TNI in SFTS patients may be useful in predicting the occurrence of IPA.